Positive Affect Is Inversely Associated with Mortality in Individuals without Depression - Martín-María, Natalia; Caballero, Francisco Félix; Olaya, Beatriz; Rodríguez-Artalejo, Fernando; Haro, Josep Maria; Miret, Marta; Ayuso-Mateos, José Luis (Frontiers in Psychology, 2016)
Background: Some studies have analysed the relation between well-being and mortality but a none of them have attempted to disentangle the differential influence that positive affect, negative affect, and evaluative well-being might have on mortality using a longitudinal design in the general population and measuring independently and accurately each component of well-being. The aim of the present study is to assess the association of these well-being components with mortality after adjusting for health and other lifestyle factors and to analyze whether this association is different in people with and without depression. Methods: A nationally representative sample of 4753 people from Spain was followed up after three years. Analyses were performed with Cox regression models among the total sample and separately in people with and without depression. Results: In the analyses adjusted for age, sex and years of education, all three well-being variables showed a statistically significant association with mortality. However, after adjustment for health status and other confounders including the well-being components, only positive affect remained as marginally associated with a decreased risk of mortality in the overall sample [OR = 0.87; 95% CI = 0.73-1.03], in particular among individuals without depression [OR = 0.82; 95% CI = 0.68-0.99]. Conclusion: Positive affect is inversely associated with mortality in individuals without depression. Future research should focus on assessing interventions associated with a higher level of positive affect.